Use of Quasi-Experimental Research Designs in Education Research: Growth, Promise, and Challenges. Issue 1 (March 2020) - Gopalan, Maithreyi; Rosinger, Kelly; Ahn, Jee Bin
In the past few decades, we have seen a rapid proliferation in the use of quasi-experimental research designs in education research. This trend, stemming in part from the "credibility revolution" in the social sciences, particularly economics, is notable along with the increasing use of randomized controlled trials in the strive toward rigorous causal inference. The overarching purpose of this chapter is to explore and document the growth, applicability, promise, and limitations of quasi-experimental research designs in education research. We first provide an overview of widely used quasi-experimental research methods in this growing literature, with particular emphasis on articles from the top ranked education research journals, including those published by the American Educational Research Association. Next, we demonstrate the applicability and promise of these methods in enhancing our understanding of the causal effects of education policies and interventions using key examples and case studies culled from the extant literature across the pre-K–16 education spectrum. Finally, we explore the limitations of these methods and conclude with thoughts on how education researchers can adapt these innovative, interdisciplinary techniques to further our understanding of some of the most enduring questions in educational policy and practice.